Humanized assistance to the low birth weight infant and support to breastfeeding: Implantation of the Kangaroo Method in High Risk Maternity at a university hospital of Vitória - Carvalho Caser, Larissa; Costa Souza, Camila; Maciel da Silva Brito, Geórgia; Maciel da Silva Brito, Lourenço; Zaganell, Francisco Luiz; Moreira Garcia Zanni, Natalia; Alves Bezerra Morais, Paloma; Cunha Fagundes , Vinicius (Guará Journal, 2017)
The objective of this study is to determine the length of hospital stay that applies the Kangaroo Method and to outline some aspects of the profile of mothers and children. A retrospective, descriptive cohort study of 87 mothers and newborns attended at a University Hospital in Vitória, Espírito Santo, between June 2015 and February 2017. A total of 22.61% of adolescents, 15.5% were elderly, 61.2% were married, 90.8% were first and second grades, 38.37% had pathology, 60.00% had 6 and more consultations and 60% underwent cesarean sections. As for the children, 51.7% were male, 92.77% were premature, 91.65% were underweight, and they had a stay of 948 days before going home and consequently reducing the cost of the day of the NICU. This analysis would be fundamental for the managers, in the quest to quantify the total volume of resources saved with the implementation of the Kangaroo Method.